Mental toughness of youth futsal athletes cimahi city - Prayoga, Arief Anugrah Sendhika; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (Jurnal Patriot, 2024)
Problem: This research was conducted because there are still less who understand the importance of this mental training, therefore the authors conducted research to find out that mental toughness greatly affects the athlete's game. Purpose: to determine the mental toughness of teenage futsal athletes in cimahi city. Methods: This research uses descriptive methods with a quantitative approach. The sample in this study consisted of 13 futsal athletes from SMAN 1 Cimahi City. The research instrument used is the Sports Mental Toughness Questionnaire (SMTQ). Data analysis was carried out by presenting the percentage of research results.Results: The results showed that Cimahi City youth futsal athletes had different percentage values of mental toughness, the highest percentage was 80% and the lowest percentage was 52%. Overall, Cimahi City youth futsal athletes have a percentage of 62%. Conclusion: This study concluded that Cimahi City youth futsal athletes already have mental toughness, but still need to be improved because they do not have a good percentage. Therefore, the author can suggest to coaches to pay more attention to psychological aspects, especially mental toughness so that athletes can undergo training more completely and not give up easily.